Implementasi Program Keluarga Harapan Di Kelurahan Sumber Sari Kecamatan Sei Tualang Raso Kota Tanjungbalai - Herlina, Herlina; Warjio, Warjio; Siregar, Nina Siti Salmaniah (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
The objectives of this study are: 1. to find out how the implementation of Hope Family Program (PKH) in Sumber Sari Sub-District, Sei Tualang Raso District, Tanjungbalai town. 2. Implementation of Family Hope Program (PKH) in the Sumber Sari Sub-District, Sei Tualang Raso District, Tanjungbalai town. This research used theory of implementation approach of policy by Daniel Mazmanian and Paul Sabatier. This theory sees the variable in controlling the problem. The variable of ability of policy in structuring the implementation process accurately and variable from outside of policy that influence the implementation process. This research used descriptive methodology with qualitative approach. The data collecting was done by monitoring and interview thoroughly. The results of this research show that the implementation of PKH in Sumber Sari Sub-District has a slight problem and has not been fully implemented properly. The socialization has not been comprehensive, so there is less support from related parties. Data collection of PKH recipient participants has not been maximized, there are some families who should get PKH but have not yet obtained it. Mentoring has not been done well and the use of PKH funds by RTSM is sometimes used outside the provisions. For the long term, it has not been able to change the mindset and behavior of the RTSM significantly.